Optimalisasi Proses Pendaftaran Siswa Baru dengan Sistem Informasi Berbasis Komputer - Salam, Abdus; Afkar, M.Khadafi; Riza, Muhammad (Jurnal Manajemen Sistem Informasi (JMASIF), 2023)
The development of a computer-based information system aims to replace the inefficient manual system in managing student data. This system was designed using Microsoft Visual BASIC 6.0 and Microsoft Access 2007 to enhance the accuracy, efficiency, and effectiveness of the student registration process. The methodology includes needs analysis, system design, implementation, and user training phases. The results indicate that the new system significantly reduces data processing time, improves information retrieval speed, and minimizes the risk of manual errors. The system comprises modules for data input, report management, and data validation, tailored to meet the professional needs of educational institutions. Flowcharts were utilized to visualize system workflows, facilitating validation processes and ensuring the feasibility of the design. The implementation of this information system enables educational institutions to optimize student data management in a more structured and reliable manner. This study confirms that the application of information technology in education has a significant impact on operational efficiency and effectiveness, providing solutions to challenges encountered in previous manual systems.